Teologia e sociedade: o papel social da igreja frente aos desafios educacionais num mundo em transição - Sampaio, Fabio Maia (2015)
To think about the relation between church and world in modernity and in post-modernity implies perceiving that this relation develops in the midst of changes characteristic of a period in which there is a need to rethink political, economical structures and religious institutions which are no longer able to respond in a satisfactory way to a society in transition. One of the challenges which education in contemporary times needs to face is that the path of a society which is ever more aware of its role in the world must go through quality education, which pervades differences, which knows how to serve in an intelligent way a much more demanding generation and one which fights for its ideals in the direction of a better world. The history of humanity is marked by the presence of religion which, in each culture, is constituted in various different ways and precisely because of this reason we cannot analyze the religious aspect in the schools in a judgmental way, much less face this reality as if it were distant from modern society. To the contrary, one seeks to find the best way to offer Religious Education (RE), considering that, in a society which is constantly modernizing, in which transformation becomes necessary to attend to the various demands, RE needs to also be part of this process, so as to respond to the religious needs of the society, respecting its cultural values. In this sense, the educational process in the country which passes through the religious vein, begins in the State of Bahia, as of the 19th century to conceive new perceptions about Religious Education which seeks to disconnect itself from the initial proposal brought by the colonizers, needing to rethink this curricular component in the perspective of inter-religious dialog, as affirmed in the article of the LDB (Lei de Diretrizes e Bases Law of Guidelines and Foundations) in the new redaction given by the law 9475/97. However, this research reveals that its implementation in the public schools is still a long path to be walked.